HE, SHE, IT, THEY – the school experience of queer teenagers - Joanna Szewczyk-Kowalczyk (Studia z Teorii Wychowania)
This paper is the result of empirical qualitative research on non-normative gender identification of teenagers studying in Lodz high schools. The presented research based on queer categories is embedded in the theory of discourse and refers to considerations about the formation of identity.